One-carbon metabolism factors and leukocyte telomere length(1)(2)(3)(4) - Liu, Jason J (American Society for Nutrition, 2013)
Background: Dietary and genetic factors involved in the one-carbon metabolism pathway may affect telomere length through DNA methylation and synthesis, but this has not been comprehensively investigated in epidemiologic studies. Objective: We cross-sectionally examined associations between dietary and genetic factors in the one-carbon metabolism pathway and relative peripheral blood leukocyte telomere length. Design: A total of 1715 participants from the Nurses’ Health Study (NHS) had measurements of relative telomere length and plasma concentrations of folate, vitamin B-6, vitamin B-12, cysteine, and homocysteine. Food-frequency questionnaire (FFQ) measurements were also used for the assessment of folate, choline, methionine, riboflavin, vitamin B-6, vitamin B-12, and alcohol intakes. Genotyping was performed on 475 participants with telomere measurements on 29 mostly nonsynonymous single-nucleotide polymorphisms (SNPs) involved in one-carbon metabolism. Unconditional logistic and linear regression models were used. Results: There were no significant dose-response relations between any plasma- or FFQ-measured dietary factors and relative telomere length in multivariate analyses. For folate, vitamin B-6, and vitamin B-12, results from the use of FFQ data were consistent with plasma-biomarker findings. We showed no significant associations that involved SNPs and relative telomere length after we accounted for the false discovery rate. Conclusion: Our analyses involving plasma and questionnaire measurements of one-carbon metabolism factors show that some key dietary and genetic factors in this metabolic network are not associated with relative peripheral blood leukocyte telomere length.